Presentation of the debate on the book The Argentine political leadership: from the National Organization to the Centennial, edited by Beatriz Bragoni, Eduardo Míguez and Gustavo Paz - La Dirección del Instituto Ravignani (Boletín del Instituto de Historia Argentina y Americana Dr. Emilio Ravignani, 2024)
Presentation